2014
DOI: 10.1177/1948550614538461
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and Objective Hierarchies and Their Relations to Psychological Well-Being

Abstract: Hierarchy can be conceptualized as objective social status (e.g., education level) or subjective social status (i.e., one’s own judgment of one’s status). Both forms predict well-being. This is the first investigation of the relative strength of these hierarchy-well-being relationships in the U.S. and Japan, cultural contexts with different normative ideas about how social status is understood and conferred. In probability samples of Japanese (N=1027) and U.S. (N=1805) adults, subjective social status more str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 59 publications
1
79
1
2
Order By: Relevance
“…Educational attainment or highest educational qualification (HEQ) is the most frequently used index of socioeconomic status and is a strong indicator of SES (Backlund, Sorlie, & Johnson, 1999;Curhan et al, 2014;Kraus, Rheinschmidt, & Piff, 2012;Lareau & Conley, 2008). Among the traditional indicators of SES-income, occupation, and education-HEQ also shows the strongest relationship with a range of outcomes, including lifestyle variables, beliefs, and functioning (Attewell & Newman, 2010;Reardon, 2011;Trautmann et al, 2013).…”
Section: The Current Investigationmentioning
confidence: 99%
“…Educational attainment or highest educational qualification (HEQ) is the most frequently used index of socioeconomic status and is a strong indicator of SES (Backlund, Sorlie, & Johnson, 1999;Curhan et al, 2014;Kraus, Rheinschmidt, & Piff, 2012;Lareau & Conley, 2008). Among the traditional indicators of SES-income, occupation, and education-HEQ also shows the strongest relationship with a range of outcomes, including lifestyle variables, beliefs, and functioning (Attewell & Newman, 2010;Reardon, 2011;Trautmann et al, 2013).…”
Section: The Current Investigationmentioning
confidence: 99%
“…Utilizing Ryff's approach, the results showed that certain subjective aspects, which predicted purpose in life and self-acceptance, had higher associations in the U.S. while other objective aspects, which predicted positive relations with others and self-acceptance, were more strongly related in Japan. Overall, the results suggested that the relationship between social hierarchy and individual well-being differed with cultural context [7]. What the results also suggest, however, is that cultural perceptions may have affected the way subjects responded to the questionnaire.…”
Section: Introductionmentioning
confidence: 68%
“…Objective status was defined as social status that is recognized by society (occupation, level of education, etc. ), whereas subjective status was based around the individual's "own view of where they stand in the social hierarchy" [7]. Utilizing Ryff's approach, the results showed that certain subjective aspects, which predicted purpose in life and self-acceptance, had higher associations in the U.S. while other objective aspects, which predicted positive relations with others and self-acceptance, were more strongly related in Japan.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In other work using nationally representative samples, subjective social class was found to predict the well-being of American participants more strongly than Japanese participants, while the opposite was found with objective social class (Curhan et al, 2014). In accounting for these independent influences, it has been argued that subjective social class is a broader conceptualization of social class, which includes objective assessments, as well as more qualitative and psychological perceptions of relative deprivation and financial security (Singh-Manoux et al, 2005;Tan, Kraus, & Adler, in prep).…”
Section: Social Class Warmth and Candidate Supportmentioning
confidence: 75%